ChemInform Abstract: Characterization, Synthesis and Catalysis of Hydrotalcite‐Related Materials for Highly Efficient Materials Transformations. Issue 40 (12th September 2013) - Nishimura, Shun; Takagaki, Atsushi; Ebitani, Kohki
Abstract Review: 142 refs.